Low-Loss Photonic Reservoir Computing with Multimode Photonic Integrated Circuits - Katumba, Andrew; Heyvaert, Jelle; Schneider, Bendix; Uvin, Sarah; Dambre, Joni; Bienstman, Peter (Scientific reports, 2018)
We present a numerical study of a passive integrated photonics reservoir computing platform based on multimodal Y-junctions. We propose a novel design of this junction where the level of adiabaticity is carefully tailored to capture the radiation loss in higher-order modes, while at the same time providing additional mode mixing that increases the richness of the reservoir dynamics. With this design, we report an overall average combination efficiency of 61% compared to the standard 50% for the singlemode case. We demonstrate that with this design, much more power is able to reach the distant nodes of the reservoir, leading to increased scaling prospects. We use the example of a header recognition task to confirm that such a reservoir can be used for bit-level processing tasks. The design itself is CMOScompatible and can be fabricated through the known standard fabrication procedures.
Keywords: Photonic Reservoir Computing; Multimode Photonic; Integrated Circuits